Development of Interactive Digital Module Based on Virtual Laboratories in The Covid-19 Pandemic Era in Dynamic Fluid Materials - Kusyanti, Rita Nunung Tri (International Journal of Active Learning, 2021)
Research and development for distance learning has been carried out during the Covid-19 pandemic which has produced learning media in the form of an interactive digital physics module based on a virtual laboratory for dynamic fluid material. At the development stage, the research was carried out at SMAN 1 Tempel, to test the use of modules in class XI MIPA1. The research method used is the theory of research and development (research and development) or R & D by Sugiyono. The module view uses the Flip PDF Professional application and the content is self-learning videos with the vokoscreen application, youtube link, PHET application, Quizizz. The digital module was validated by media expert lecturers and material content experts, as well as module trials by 35 students of class XI MIPA1. The results of the validation of the media expert obtained 92.36%, the expert validation of the material content was 86% so that the expert validation obtained by the classification of the module was very valid / very feasible to use. The results of student responses using the module gave an average response of 87.8% with a good category, with an average quiz result of 78.These results indicate that the use of interactive digital modules based on virtual laboratories on dynamic fluid material is very feasible, easy, and attracts students to studied physics at home during the C-19 pandemic.